Radiative efficiency of lead iodide based perovskite solar cells - Tvingstedt, K; Malinkiewicz, O; Baumann, A; Deibel, C; Snaith, H; Dyakonov, V; Bolink, H (Springer Nature, 2014)
The maximum efficiency of any solar cell can be evaluated in terms of its corresponding ability to emit light. We herein determine the important figure of merit of radiative efficiency for Methylammonium Lead Iodide perovskite solar cells and, to put in context, relate it to an organic photovoltaic (OPV) model device. We evaluate the reciprocity relation between electroluminescence and photovoltaic quantum efficiency and conclude that the emission from the perovskite devices is dominated by a sharp band-to-band transition that has a radiative efficiency much higher than that of an average OPV device. As a consequence, the perovskite have the benefit of retaining an open circuit voltage ~0.14 V closer to its radiative limit than the OPV cell. Additionally, and in contrast to OPVs, we show that the photoluminescence of the perovskite solar cell is substantially quenched under short circuit conditions in accordance with how an ideal photovoltaic cell should operate.